Effect of corn gluten feed or corn dried distiller grains with solubles as a substitute for soybean meal of Boer-type goat - Kim, Eunji; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
Goat populations have increased over the past few years. Because slaughter numbers of goats increased about 7 percent last year to 2.07 million, and exports gained 6 percent to 28.4 million ton (Bloomberg 2018). The advantage, for products are that they are an inexpensive protein source that is highly available in the Midwest. There is little research evaluating different ingredients on goat growth performance. Therefore, the objective of this experiment was to determine how corn gluten feed (CFG) or corn dried distillers’ grains with solubles (DDGS) could impact goat growth performance, and economics with soybean meal (SBM). Treatments were isocaloric and isonitrogenous but varied in protein source: 1) soybean meal; 2) 100% DDGS/0% CGF; 3) 66% DDGS/33% CGF; 4) 33% DDGS/66% CGF; 5) 0% DDGS/100% CGF and fed to seventy-five Boer-type goats (26.9±0.2 kg). There were 3 goats per pen and 5 pens per treatment for 35 days in a completely randomized design. The experimental unit was housed pens. Data was analyzed using the GLIMMIX procedures of SAS (v. 9.4, Cary, NC), with 0.05 as the accepted alpha. Overall, diet had no obscene impact on growth (P>0.05). However, it did impact on feed cost per goat. Feed cost per kg was lower in corn co-products than soybean meal as the protein source. This $0.04/kg of feed decrease in feed cost, resulted lower (P = 0.0008) feed cost/goat for goats fed corn co-products compared to SBM. In summary, CGF or DDGS may be a cost-effective replacement for SBM in goat diets, with no detected impact in growth.
Keywords: Spring 2019